2020
DOI: 10.2147/ndt.s277303
|View full text |Cite
|
Sign up to set email alerts
|

<p>Care Needs of Community-Residing Male Patients with Vascular Cognitive Impairment</p>

Abstract: The aim of this study was to identify the care needs of male patients with vascular cognitive impairment (VCI) and their caregivers. Patients and Methods: This cross-sectional study enrolled 389 male patients with VCI and their caregivers who were cared for by the dementia collaborative care team at Changhua Christian Hospital, Taiwan. Fifteen care needs consisting of most of quality measures for people living with dementia and their caregivers were developed by the care team. Through face-to-face evaluations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…27,28 The Apriori algorithm, which has been applied in dementia-related studies, was employed in this study to find statistical associations between any of the attributes by satisfying both minimum support and confidence threshold values along with lift >1. 6,7,[29][30][31][32][33] The definitions of support, confidence, and lift are depicted as below. 6,29,32,33 The support of A ⇒ B calculates the percentage of transactions containing both A and B in the database depicted in Equation ( 1…”
mentioning
confidence: 99%
“…27,28 The Apriori algorithm, which has been applied in dementia-related studies, was employed in this study to find statistical associations between any of the attributes by satisfying both minimum support and confidence threshold values along with lift >1. 6,7,[29][30][31][32][33] The definitions of support, confidence, and lift are depicted as below. 6,29,32,33 The support of A ⇒ B calculates the percentage of transactions containing both A and B in the database depicted in Equation ( 1…”
mentioning
confidence: 99%
“…The Apriori algorithm was applied to reveal statistical correlations from a multidimensional viewpoint when each attribute was viewed as a dimension by setting up support, confidence, and lift. 12 , 13 , 22 , 23 Yan et al 11 reported that the Apriori algorithm was very effective for identifying caregiving burden levels when patients with dementia and their caregivers were taken into account simultaneously. Therefore, the Apriori algorithm was employed in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The definitions of support, confidence, and lift are as follows. 11 , 22 , 23 The support of an association rule A ⇒ B is used to compute the percentage of transactions containing both A and B in the database, as shown in Equation (1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The definitions are as follows. 16,19,20 The support of A ⇒ B is evaluated by calculating the percentage of transactions in the database containing both A and B: Support ðA ) BÞ ¼ P A\B ð Þ ¼ number of transactions containing both A and B total number of transactions (1)…”
Section: Methodsmentioning
confidence: 99%